2020
DOI: 10.1093/cercor/bhaa276
|View full text |Cite
|
Sign up to set email alerts
|

First Demonstration of Double Dissociation between COMT-Met158 and COMT-Val158 Cognitive Performance When Stressed and When Calmer

Abstract: We present here the first evidence of the much-predicted double dissociation between the effect of stress on cognitive skills [executive functions (EFs)] dependent on prefrontal cortex (PFC) by catechol-O-methyltransferase (COMT) genotype. The COMT gene polymorphism with methionine (Met) at codon 158 results in more dopamine (DA) in PFC and generally better EFs, while with valine (Val) at codon 158 the result is less PFC DA and generally poorer EFs. Many have predicted that mild stress, by raising PFC DA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Dopamine dysfunction in the PFC and striatum has been shown to shape schizophrenia in particular (Durstewitz & Seamans, 2008;Simpson, Kellendonk, & Kandel, 2010). Defining the dopaminergic basis of inflexible behavior is therefore critical for advancing psychopharmacological research and for understanding paradoxical or personalized treatment effects (Cools, 2019;Durstewitz & Seamans, 2008) as well as the effects of stress (Diamond, 2011;Zareyan et al, 2021). The implications of our observations are that the cognitive enhancing effects of dopaminergic agonists will be most prominent in individuals with low IQ, or presumably also, low working memory capacity.…”
Section: Discussionmentioning
confidence: 82%
“…Dopamine dysfunction in the PFC and striatum has been shown to shape schizophrenia in particular (Durstewitz & Seamans, 2008;Simpson, Kellendonk, & Kandel, 2010). Defining the dopaminergic basis of inflexible behavior is therefore critical for advancing psychopharmacological research and for understanding paradoxical or personalized treatment effects (Cools, 2019;Durstewitz & Seamans, 2008) as well as the effects of stress (Diamond, 2011;Zareyan et al, 2021). The implications of our observations are that the cognitive enhancing effects of dopaminergic agonists will be most prominent in individuals with low IQ, or presumably also, low working memory capacity.…”
Section: Discussionmentioning
confidence: 82%
“…The learning of "how to describe or assess uncertainty" would be of universal concern for all students. A recent dopamine study showed that most people could not use the "very mild stress" as stimulation to increase their executive function capability, in contrary to the common expectation that a small amount of stress for the raising of dopamine could facilitate the executive function in the cognition process (Zareyan, et al, 2020). Familiarity with the uncertainty in introductory astronomy would be transferred to a deeper understanding of uncertainty in general and could reduce daily life stress due to uncertainty.…”
Section: Finding and Discussionmentioning
confidence: 94%
“…In contrast to the dlPFC, high levels of catecholamines and glucocorticoids enhance the affective functioning of the amygdala (81)(82)(83), thus flipping the brain from a reflective to reflexive state. The rapid loss of dlPFC executive and working memory functions from a hypercatecholaminergic state has now been documented in humans (84)(85)(86) in addition to the original studies in rodents and monkeys (9,77,78). Thus, BA25 and amygdala can rapidly remove their regulation from higher order PFC circuits through activation of excessive catecholamine release in these higher PFC regions (Figure 4B).…”
Section: Figure 4 | (A)mentioning
confidence: 87%